Use of Maribavir for Multidrug-Resistant Cytomegalovirus in an Immunocompromised Host With HIV and Common Variable Immunodeficiency - Diana Zarowin; Jared Coe; Maxwell Bressman; Paul Riska; Philip Yune; Ghaleb Halaseh; Matthew J. Akiyama (Annals of Internal Medicine: Clinical Cases)
We present a case of multidrug-resistant Cytomegalovirus (CMV) and the use of maribavir, a novel oral treatment of resistant CMV, in a nontransplant immunocompromised host. Our patient initially was diagnosed with CMV pharyngitis on biopsy. Although his initial CMV pharyngitis resolved, the CMV isolated from blood became resistant to ganciclovir and cidofovir and eventually required treatment with foscarnet. Our patient was given a trial of maribavir. After 6 weeks, the patient's viremia resolved and remained undetectable for 6 months after treatment initiation with maribavir. This case demonstrates the feasibility of using maribavir for resistant CMV in a nontransplant, immunocompromised patient.